Effects of the Pelleting Process on Diet Formulations with Varying Levels of Crystalline Amino Acids and Reducing Sugars on Nursery Pig Growth Performance - Kara M. Dunmire; Michaela B. Braun; Yiqin Zhang; Cassandra K. Jones; Yonghui Li; Jason C. Woodworth; Robert D. Goodband; Mike D. Tokach; Adam C. Fahrenholz; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
Pelleting swine feed and the use of crystalline amino acids and by-product ingredients can potentially create ideal conditions that further facilitate the Maillard browning reaction. The Maillard reaction combines an amino group of a free amino acid and a carbonyl group of a reducing sugar (RS), making the amino acid less available. The objective of this study was to determine the effects of pelleting swine diets containing free amino acids and reducing sugars at high temperatures on nursery pig growth performance. A total of 360 pigs (initially 25.0 lb; Line 200 × 400; DNA, Columbus, NE) were used in a study evaluating the effect of crystalline AA, reducing sugars, and feed form on growth performance of nursery pigs. Treatments were arranged in a 2 × 2 × 2 factorial with main effects of crystalline AA concentration (low vs. high), reducing sugars (RS; low vs. high), and diet form (mash vs. pellet). Diets were formulated with low or high crystalline AA and low or high reducing sugars provided by co-product ingredients, DDGS and bakery meal. Diets were pelleted to a conditioning temperature of 187.5°F. When pigs weighed approximately 25 lb, they were weighed, and pens were randomly assigned treatments. There were 9 replications per treatment and 5 pigs per pen. There were no 3-way or 2-way interactions. For the main effect of form, there was no evidence of difference in ADG, and ADFI increased (P= 0.001) in pigs fed mash diets compared to pellets. Feed efficiency and caloric efficiency improved (P= 0.001) in pigs fed pelleted diets compared to mash diets. For the main effect of crystalline AA, there was no evidence of difference in ADG or F/G; however, pigs fed high crystalline AA had increased (P= 0.024) ADFI compared to those fed low crystalline AA diets. For the main effect of RS inclusion, pigs fed low RS diets had increased (P<0.041) ADG and ADFI compared to pigs fed high RS inclusion diets. There was an improvement (P= 0.019) in F/G and caloric efficiency for pigs fed high RS inclusion diets compared to those fed low RS diets. There was no evidence of difference in IOFC for form, crystalline AA, or RS. In conclusion, there was no evidence of interactions between diet types, indicating that increasing amounts of crystalline AA and RS did not increase the Maillard reaction or reduce growth performance when pelleting diets by using the reported conditions. Pigs fed pelleted diets had similar ADG and an 8% improvement in F/G compared to those fed mash diets. Pigs fed the high RS diets had reduced feed intake, which resulted in reduced gain and improved feed and caloric efficiency. Additionally, pigs fed high AA diets had increased feed intake.
Keywords: amino acids; reducing sugars; pelleting; nursery pigs